Distinction: A Social Critique of the Judgement of Taste - Пьер Бурдье (Journal of Economic Sociology, 2010)
We publish here the main part of Bourdieu text, which comprises of the fragments of his famous book “Distinction: A Social Critique of the Judgement of Taste” (D. Gruski is responsible for the pages for choice).